Market leader interactive high English for successful business communication - Pearson Education Inc. ([S.l.] : Pearson Education, 2003)
Single-user version
System requirements : Windows 98, Windows 2000 with service pack 2 (or higher), or NT 4.0 with service pack 5 (or higher)
Keywords: English language -- Business English